Validasi Bahan Ajar Fisika Berbasis Inkuiri pada Materi Hukum Newton Tentang Gerak dan Gravitasi untuk Meningkatkan Literasi Sains - Desi Deswita; Hufri Hufri (PILLAR OF PHYSICS EDUCATION, 2018)
This research is based on the low science literacy of student and the teaching materials used in the lessons have not facilitated the students to increase their science literacy. The purpose of this study was to develop inquiry-based physics teaching materials and to determine the validity of inquiry-based physics-based materials on newton's law materials about motion and gravity to increase the science literacy of high school students of class X. The type of research used Research and development (R & D) research steps: potential and problems, data collection, product design, design validation, design revisions, product trials and product revisions. While the data analysis used is descriptive data analysis. The instrument used is validation sheet that has been validated by experts. Based on the results of validation by experts, the instruments used are at very valid criteria with an average value of 90.83.The results obtained consist of 2 results. First, generated inquiry-based teaching materials. Second, the results of the validation analysis show that the resultant inquiry-based teaching materials are at a very valid level with a value of 82.78.